Biotransformação de cicloadutos de Diels-Alder por células intactas de Penicillium brasilianum, endofítico de Melia azedarach - Santos, Ana Carolina Alves dos (2014)
Endophytic microorganisms have a great enzymatic potential to biotransformate substances of natural and synthetic origin due to strategies developed during colonization to coexist with the plant in an initial hostile environment. Microbial transformation of Diels-Alder cycloadducts were trailed by the endophyte P. brasilianum using intact cells and resulted in the production of several products (17). These products were identified as products of chlorination (Q4_F2_15), epoxidation (Q1A_CR_16, Q2A_CR_6, Q3A_CR_5), epoxidation and reduction of conjugated double bond (Q2A_CR_5), reduction of conjugated double bond (Q2A_CR_9, Q3A_CR_7_pico2, Q3A_CR_8, Q4A_CR_23), reduction of isolated double bond (Q1A_CR_26), oxidation of allilic methyl group and reduction of conjugated double bond (Q4A_CR_10), reduction of carbonyl and conjugated double bond (Q4A_CR_20), reduction of carbonyl and ether formation (Q5A_CR_15) and finally, reduction of carbonyl group (Q4A_CR_15 e Q5A_CR_18). The reduction of conjugated double bond can be performed by enzymes called Old Yellow Enzymes (OYE), also known as enoate reductase enzymes. The products of carbonilic or double bond reduction were also synthesized chemically and the enantioselectivity of both in vitro and in vivo process were compared. In all cases, microbiological transformations were more enantioselectivity.